Simultaneous multi-wavelength phase-shifting interferometry based on principal component analysis with a color CMOS. (15th March 2016) - Fan, Jingping; Lu, Xiaoxu; Xu, Xiaofei; Zhong, Liyun
Abstract: From a sequence of simultaneous multi-wavelength phase-shifting interferograms (SMWPSIs) recorded by a color CMOS, a principal component analysis (PCA) based multi-wavelength interferometry (MWI) is proposed. First, a sequence of SMWPSIs with unknown phase shifts are recorded with a single-chip color CMOS camera. Subsequently, the wrapped phases of single-wavelength are retrieved with the PCA algorithm. Finally, the unambiguous phase of the extended synthetic wavelength is achieved by the subtraction between the wrapped phases of single-wavelength. In addition, to eliminate the additional phase introduced by the microscope and intensity crosstalk among three-color channels, a two-step phase compensation method with and without the measured object in the experimental system is employed. Compared with conventional single-wavelength phase-shifting interferometry, due to no requirements for phase shifts calibration and the phase unwrapping operation, the actual unambiguous phase of the measured object can be achieved with the proposed PCA-based MWI method conveniently. Both numerical simulations and experimental results demonstrate that the proposed PCA-based MWI method can enlarge not only the measuring range, but also no amplification of noise level.